(untitled) (Bangladesh Journal of Animal Science, 2018)
The present study was conducted to know the production and reproduction potentials, and egg quality characteristics of Nageswari duck under intensive management condition. Data were collected from a nucleus flock of Nageswari ducks that have been maintained from day old to 72 weeks of age at AI center, Bangladesh Agricultural University, Mymensingh, from May 2015 to October 2016. Irrespective of sex, the average live weight of ducklings at day old, 1st, 3rd, 5th, 7thand 9thweeks of age were observed to be 38.85±1.40, 99.06±2.93, 373.29±8.73, 650.31±11.26, 867.74±11.79 and 1076.11±16.34 g, respectively. There was a steady increasing trend observed in live weights for both drakes and ducks from 17thto 72 weeks of age. The average age of sexual maturity and weight were found 130±1.83 days and 1400.84±12.68g respectively. The average egg weight and annual egg production were 58.20±1.50g and 204.23±14.19 no’s, respectively. Hen day egg production was found 55.67±2.74% while the peak production was observed at 26th week of age. The estimated mean egg mass production (g/b/day), feed intake(g) during laying, feed conversion efficiency and performance efficiency index of Nageswari duck were 32.40±2.29, 154.85±2.27, 4.63±0.21 and 20.92±1.37, respectively in Nageswari duck. The external egg quality characteristics like shape index, egg breaking strength, shell thickness and membrane thickness were observed to be 74.59±0.61, 2.00±0.03 kg/cm2, 3.99±0.06 mm and 0.50 ± 0.02 mm respectively whereas, internal quality attributes such as albumen index, yolk index, yolk color score and Haugh unit were 8.89±0.29, 34.36±0.61, 8.42±0.28 and 86.29±1.06, respectively. In conclusion, the studied parameters of Nageswari duck provided some breed specific baseline information and year round actual production potentials of this genetic resource under intensive management condition that could be utilized for future conservation and breeding programs in Bangladesh. Bang. J. Anim. Sci. 2017. 46 (3): 198-205